Who should determine energy efficiency level in a green cost-sharing supply chain with learning effect?. (January 2018) - Zhang, Qiao; Tang, Wansheng; Zhang, Jianxiong
Highlights: A dynamic cost learning effect is considered in a cost-sharing green supply chain. Decision rights of EE level held by manufacturer or retailer are respectively studied. Equilibrium strategies in the two cases are the same if the cost-sharing rate is 1/2. The retailer abandons the decision right except for a large bargaining power. The retailer's preference on the decision right is weakened by cost learning effect. Abstract: The increasing environmental awareness and green demands drive channel members to jointly take efforts to improve energy efficiency level of products. Considering the cost learning effect, this work develops a differential game model where the retailer (leader) sets retail margin, the manufacturer (follower) determines wholesale price and they jointly invest in energy efficiency level. Two scenarios are considered, where the decision right of energy efficiency level is respectively held by manufacturer (ME) and retailer (RE). Main results indicate that the energy efficiency level is usually governed by the manufacturer rather than the retailer, unless the retailer has a large bargaining power. Besides, the retailer's preference on the decision right is weakened by a larger cost learning effect or energy efficiency effectiveness, but improved by a greater investment cost. This work contributes to researches of the channel members' preference on holding the decision right of energy efficiency level in the presence of cost learning effect, and provides important managerial insights on firms' investment and pricing strategies.